Personnel testing : a manager's guide - Jones, John W (Crisp Pub. Menlo ParkUS, 1994)
Defines a personnel test and lists benefits of personnel testing. Lists six situations for which companies use personnel tests, viz., personnel selection, placement, career counselling, vocational education, training and development, and personnel research. Discusses the nine-step scientific assessment model. Provides guidelines for implementing a personnel testing programme, and for administering a personnel test. Gives insight into content format and test assessment procedures. Outlines legal guidelines; key requirements of professional standards; and government regulations to which employees must adhere.